Premature senescence and cardiovascular disease following cancer treatments: mechanistic insights - Jain, Ashita; Casanova, Diego; Padilla, Alejandra Valdivia; Paniagua Bojorges, Angelica; Kotla, Sivareddy; Ko, Kyung Ae; Samanthapudi, Venkata S. K.; Chau, Khanh; Nguyen, Minh T. H.; Wen, Jake; Hernandez Gonzalez, Selina L.; Rodgers, Shaefali P.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular disease (CVD) is a leading cause of morbidity and mortality, especially among the aging population. The “response-to-injury” model proposed by Dr. Russell Ross in 1999 emphasizes inflammation as a critical factor in atherosclerosis development, with atherosclerotic plaques forming due to endothelial cell (EC) injury, followed by myeloid cell adhesion and invasion into the blood vessel walls. Recent evidence indicates that cancer and its treatments can lead to long-term complications, including CVD. Cellular senescence, a hallmark of aging, is implicated in CVD pathogenesis, particularly in cancer survivors. However, the precise mechanisms linking premature senescence to CVD in cancer survivors remain poorly understood. This article aims to provide mechanistic insights into this association and propose future directions to better comprehend this complex interplay.